ANTIMICROBIAL SUSCEPTIBILITY OF 51 CAMPYLOBACTER STRAINS ISOLATED FROM DIARRHEIC AND DIARRHEA-FREE DOGS* - Modolo, J.r. [UNESP] (2024)
The minimum inhibitory concentrations (MICs) were determined by agar dilution for six antimicrobial agents (cephalexin, eythromycin, gentamicin, enrofloxacin, chloramphenicol, and oxytetracyline) using 51 Campylobacter strains (29 Campylobacter jejuni subsp. jejuni, 14 Campylobacter jejuni subsp doylei, 5 Campylobacter upsaliensis, 2 Campylobacter coli, and 1 Campylobacter lari) isolated from 29 diarrheic and 22 diarrhea-free dogs. Percentages corresponding to 50% and 90% strain inhibition (MIC 50% and MIC 90%) were determined. The results show that erythromycin, enrofloxacin, and gentamicin can be recommended for the treatment of campylobacteriosis in dogs; this opens the possibility of their therapeutic use in human medicine.